Chairside molecular imaging of aberrant glycosylation in subjects with suspicious oral lesions using fluorescently labeled wheat germ agglutinin. Issue 2 (30th September 2017) - Baeten, John; Johnson, Alexander; Sunny, Sumsum; Suresh, Amritha; Birur, Praveen; Uma, K; Kademani, Deepak
Abstract: Background: Aberrant sialylation is accepted as a carcinogenic biomarker. In previous work, fluorescently labeled wheat germ agglutinin (WGA) distinguished between cancerous and normal oral biopsies. The purpose of this study was to investigate WGA‐fluorescein isothiocyanate (FITC) as a point‐of‐care tool for detecting oral malignant and dysplastic lesions in vivo. Methods: Subject recruitment was divided into two groups: (1) the clinically normal oral mucosa group; or (2) the presence of clinically suspicious oral lesion(s) group. A WGA‐FITC solution was topically applied to observable lesions or to half the subject's mouth (sagittal plane) if lesions were absent. Fluorescent molecular imaging was used to evaluate WGA‐FITC localization. Results: Fluorescent imaging in 55 subjects demonstrated that WGA‐FITC could detect histopathologically‐confirmed cancerous and dysplastic lesions with high sensitivity (100% and 81%, respectively) and specificity (82%). Conclusion: This study supports in vivo fluorescent molecular imaging of WGA‐FITC to visualize aberrant sialic acid expression associated with carcinogenesis. This technique resulted in the immediate chairside detection of oral cancerous and dysplastic lesions.